Pravna ureditev trgovine z ljudmi v Sloveniji - Banič, Margerita J. (Teorija in praksa, 2024)
The article analyses the Slovenian legislation on human trafficking and the challenges the phenomenon creates during the time of the war in Ukraine. Victims of human trafficking are deceived by promises to improve their social situation, and often trapped in a vicious circle of physical, psychological and economic violence. Raising awareness among professionals and the general public is especially crucial in times of instability in Europe since stronger recognition of the elements of human trafficking can lead to more traffickers being convicted.
Keywords: človekove pravice; economic abuse; ekonomsko nasilje; exploitation; exploitation of victims; human rights; modern slavery; moderno suženjstvo; Pravna varnost; pregon; pregon trgovcev z ljudmi; prosecution of perpetrators; Rusko-ukrajinska vojna (2014-....); trafficking in human beings; trgovci z ljudmi; Trgovina z ljudmi; Ukrainians; Ukrajinci; victims; žrtve; žrtve trgovine z ljudmi